Experimental analysis on machining attributes in milling of nickel based super alloy Nimonic C-263. Issue 3 (3rd July 2022) - Ezilarasan, Chakaravarthy; Francis Xavier, J.; Shanmugaselvam, Palaniyandi; Balu, P.; Nagaraj, M.
ABSTRACT: Nimonic C263 is used to render parts of aircraft parts and it is difficult to cut owing to low thermal conductivity and high work hardening rate. Hence it results in high rapid tool wear and poor surface integrity during machining. The present work is carried out to find out the effects of the cutting speed, feed rate and depth of cut on surface roughness and flank wear in milling Nimonic C263 alloy with TiAlN coated carbide tool in dry environment. A predictive model was also developed to predict the surface roughness based on RSM (Response Surface Methodology).  L9 orthogonal array was used to do experimental trails. An ANOVA analysis was performed to find the impact of the machining parameters on the surface roughness. The surface roughness was increased at lower level of cutting speed, higher level of feed rate and depth of cut. The percentage contribution of feed rate, spindle speed and depth of cut on the surface roughness are as follows 55.87%, 28.68% and 0.19% respectively. The quality of the machined surfaces and the worn-out tool were analyzed using SEM images. Abrasion wear was found at higher level of feed rate.